Development of Electronic Learning Chemistry Assessment Applications Through Project-Based Learning for Increasing Student Scientific Performance - Ratih Permana Sari*; Molani Paulina Hasibuan; Coryna Oktaviani; Muhammad Yakob; Muhammad Nazar (Jurnal Pendidikan Sains Indonesia, 2023)
Today the electronic learning has developed because in line with the demands of the that sorely on technology. Assessment is one of the important elements in instructional activities and to support e-learning appear the electronic assessment. This study aims to develop an electronic learning chemistry assesment (Element) digital application through project based learning (PjBL) on the concept of applied chemistry. The research method used is the research and development method. The research subjects for the product trial developed in this study were students of the class of 2019/2020 with a purposive sampling technique with a sample of 24 students. This research instrument uses a needs analysis questionnaire, expert validation before and after revision, student response and small-scale trials. The assessment component contained in the application consists of quiz assignments, practical, product, project and final. The validation results were analyzed using content validity ratio (CVR) analysis and each criterion was then calculated the content validity index (CVI) or average value. The results showed that the Element through PjBL on applied chemistry concepts had been validated by material and media experts with an average CVI of 0.9 or the very valid category. The results of the small-scale test of the electronic-virtual assessment for of learning application for students obtained an average percentage of 93.9% with the criteria of "very interesting". Furthermore, the data on increasing students' scientific performance has increased by 0.70 with a high category and is strong effectively used to improve student scientific performance